Validity of Coagulation Activation Markers in Antiphospholipid Syndrome: A Systematic Review and Meta-analysis with a Short Data Report - Ames, Paul R.J.; Bucci, Tommaso; Iannaccone, Luigi; Marottoli, Vincenzo; Arcaro, Alessia; Gentile, Fabrizio; Ciampa, Antonio (Seminars in Thrombosis and Hemostasis, 2019)
Prothrombin fragment F1 + 2 (F1 + 2) and thrombin–antithrombin (TAT) have been assessed in antiphospholipid syndrome (APS) but without evaluating a direct relationship with antiphospholipid (aPL) antibody titers. This article aims to investigate a direct relationship between aPL and F1 + 2 and perform a systematic review and meta-analysis of F1 + 2 and TAT in APS. Systematic search was performed using EMBASE and PubMed databases from January 1982 to December 2018 and random effects meta-analyses for continuous outcomes. This is a cross-sectional case–control study; immunoglobulin G/immunoglobulin M (IgG/IgM) anticardiolipin (aCL) anti-β2-glycoprotein-I, antiprothrombin (aPT) antibodies, F1 + 2, and lupus anticoagulants (LA) were measured in 25 thrombotic primary APS (PAPS), 9 nonthrombotic carriers of aPL, and 18 controls. The significant effect size (ES) for F1 + 2 between aPL +ve and aPL −ve systemic lupus erythematosus (SLE) and between aPL +ve SLE and control displayed high heterogeneity. The significant ES for F1 + 2 between aPL −ve SLE and controls displayed no heterogeneity. The ES for TAT between aPL +ve and aPL −ve SLE patients and between aPL −ve SLE and controls was low, without heterogeneity. Mean F1 + 2 was greater in PAPS (p < 0.0001), inversely correlated with IgG aCL, IgM aPT, and LA (p = 0.001, 0.03, and 0.01, respectively), though only IgG aCL negatively predicted F1 + 2 (p = 0.01). IgG aCL inversely predicts F1 + 2. IgG aCL positivity introduces heterogeneity in the F1 + 2 ES, whereas the lack of heterogeneity in the ES for TAT may indicate poor TAT formation in aPL +ve group. Thus, F1 + 2 measurements may be unfounded as already demonstrated for TAT in the 1990s.
Keywords: antiphospholipid antibodies; prothrombin fragment 1 + 2; thrombin–antithrombin